2010
DOI: 10.1039/b9ay00313d
|View full text |Cite
|
Sign up to set email alerts
|

High temperature imidazolium ionic polymer for gas chromatography

Abstract: A new main-chain type ionic homopolymer GC stationary phase which has high separation efficiencies for alcohols, phthalates and PAHs and a maximum programmable temperature of 400 C was prepared and studied.Ionic liquids (ILs) are salts with relatively low melting points; they are usually liquid around ambient temperature. ILs have recently attracted a lot of interest due to their unique properties. Their minuscule vapor pressure and inflammability make them ''green'' solvents, in contrast to conventional organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Preparation of IL‐Based Lubricants : The synthesis method of PImC 6 NTf 2 was in accordance with that by Ho et al[14a], and BIm 5 ‐(NTf 2 ) 2 was synthesized with a similar method as reported by Gusain et al[5a] and Zeng et al[5b]. After vacuum drying at 80 °C for 12 h, the two ILs were stored at room temperature of 25 ± 3 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of IL‐Based Lubricants : The synthesis method of PImC 6 NTf 2 was in accordance with that by Ho et al[14a], and BIm 5 ‐(NTf 2 ) 2 was synthesized with a similar method as reported by Gusain et al[5a] and Zeng et al[5b]. After vacuum drying at 80 °C for 12 h, the two ILs were stored at room temperature of 25 ± 3 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Zhang et al and Bapat et al synthesized copolymerized PILs as lubricant additives which remarkably improved tribological properties in selected base oils. However, PILs generally have a higher melting point than conventional MILs and DILs, and are often present in solid form at room temperature to lose the fluidity of the lubricant, which prevents them to be directly used as lubricants . To our best knowledge, until now there is no work on the lubrication performance of PILs as base lubricant or lubricating grease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An IL-based technology can also be used to design special HPLC columns to separate PAH chiral compounds. 47 Various studies of PAHs in IL solutions have been reported, mainly in the scope of extraction applications, such as microextraction, [48][49][50][51][52][53] analytical techniques 54 such as chromatography [55][56][57] or environmental issues. 56,58 In microextraction processes, ILs act as fiber modifiers and the resulting materials are used to extract PAH analytes with higher resolution.…”
Section: A Small Survey Of the Literature On Ils Carbon Nanomaterialsmentioning
confidence: 99%
“…At high temperatures, uniform IL-coated silica columns can experience film disruption leading to a decrease in the analyte retention times and efficiency. In this regard, polymerized ionic liquids (PILs) can provide the required answers, maintaining the excellent thermal stability of the columns, and combining the main features of an ionic liquid and the typical polymer properties such as improved mechanical stability and processability [ 39 , 40 , 41 , 42 ]. Furthermore, in recent years, Anderson et al reported the development of cross-linked polymeric ionic liquid stationary phases for GC with higher thermal stability (up to 380 °C) [ 43 ] than the columns coated with the monocationic or dicationic ILs with similar structures [ 44 ].…”
Section: Introductionmentioning
confidence: 99%